Characterization of a new model of chemotherapy-induced heart failure with reduced ejection fraction and nephrotic syndrome in Ren-2 transgenic rats - Gawrys, Olga; Jíchová, Šárka; Miklovič, Matúš; Husková, Zuzana; Kikerlová, Soňa; Sadowski, Janusz; Kollárová, Petra; Lenčová-Popelova, Olga; Hošková, Lenka; Imig, John D; Mazurova, Yvona; Kolář, František; et al. (Hypertension research, 2024)
All anthracyclines, including doxorubicin (DOXO), the most common and still indispensable drug, exhibit cardiotoxicity with inherent risk of irreversible cardiomyopathy leading to heart failure with reduced ejection fraction (HFrEF). Current pharmacological strategies are clearly less effective for this type of HFrEF, hence an urgent need for new therapeutic approaches. The prerequisite for success is thorough understanding of pathophysiology of this HFrEF form, which requires an appropriate animal model of the disease. The aim of this study was to comprehensively characterise a novel model of HF with cardiorenal syndrome, i.e. DOXO-induced HFrEF with nephrotic syndrome, in which DOXO was administered to Ren-2 transgenic rats (TGR) via five intravenous injections in a cumulative dose of 10 mg/kg of body weight (BW). Our analysis included survival, echocardiography, as well as histological examination of the heart and kidneys, blood pressure, but also a broad spectrum of biomarkers to evaluate cardiac remodelling, fibrosis, apoptosis, oxidative stress and more. We have shown that the new model adequately mimics the cardiac remodelling described as "eccentric chamber atrophy" and myocardial damage typical for DOXO-related cardiotoxicity, without major damage of the peritoneum, lungs and liver. This pattern corresponds well to a clinical situation of cancer patients receiving anthracyclines, where HF develops with some delay after the anticancer therapy. Therefore, this study may serve as a comprehensive reference for all types of research on DOXO-related cardiotoxicity, proving especially useful in the search for new therapeutic strategies.
Keywords: Doxorubicin; Rats; Stroke Volume; Experimental model of heart failure; Ren-2 transgenic hypertensive rat; Disease Models, Animal; Chemotherapy induced heart failure; mužské pohlaví; Oxidative Stress; krysa rodu Rattus; Rats, Transgenic; tepový objem; modely nemocí na zvířatech; doxorubicin; zvířata; nefrotický syndrom; Nephrotic Syndrome; Antibiotics, Antineoplastic; NO/sGC/cGMP pathway; ledviny; srdeční selhání; potkani transgenní; protinádorová antibiotika; Kidney; oxidační stres; Heart Failure; Male; Animals